What David Saw: Messianic Exegesis in Acts 2 - Holladay, Carl R. (Stone-Campbell journal, 2016)
Lukes use of Psalm 16 in two speeches in Acts reflects a kerygmatic view of Christs death and resurrection. This paper explores his understanding of the psalm, informed by several OT texts, and suggests he believed David prophetically envisioned his house would continue and an heir would be raised from the dead, that David composed the psalm as a "Messianic speech" and possibly intended dual Messianic and self-referential meanings.